Green Technology Wrist Band with Patient Identification Near Field Communication (NFC) or Radio Frequency Identification (RFID) Security Features - Dahwi, MMM; Ismail, W; Afandi, RR; Husin, A; Hassan, R; Bahari, M (Amer Scientific Publishers, 2024)
Every now and then, our lives are influenced by the development of technologies and this had changed the perception of business in several ways. Now the world is focusing on wireless devices that can be developed to have exchange of data either using internet or not. Near Field Communication (NFC) is one of the devices that has the capability to securely exchange data with its paired devices and Radio-Frequency Identification (RFID) is developed to broadcast a unique identifying number upon request. This paper concentrates on the security element in the NFC and RFID in the implementation of NFC technology in blood transfusion; to solve the problems of human error and to avoid from transfusing different blood types than the ones actually needed by the patient. The information in the wrist tag should be synchronized with the current hospital system. This NFC technology is also for reducing the use of paper-based documents, consequently promoting green technology. As a result, choosing the NFC or RFID based on the security features is very important for patient identification as well as moving towards green technology.